2020
DOI: 10.1021/acs.chemmater.0c02261
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Driven Interfacial Degradation between Li7La3Zr2O12 Electrolyte and LiNi0.6Mn0.2Co0.2O2 Cathode

Abstract: Solid-state batteries offer higher energy density and enhanced safety compared to the present lithium-ion batteries using liquid electrolytes. A challenge to implement them is the high resistances, especially at the solid electrolyte interface with the cathode. Sintering at elevated temperature is needed in order to get good contact between the ceramic solid electrolyte and oxide cathodes and thus to reduce contact resistances. Many solid electrolyte and cathode materials react to form secondary phases. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 63 publications
(116 reference statements)
4
46
0
Order By: Relevance
“…Moreover, practical consideration of the environment, such as temperature and gas species involved in the synthesis, is still difficult to simulate and can lead to divergences between computational predictions and experimental observations. For example, in our recent work on LLZO-NMC and LLZO-LCO interface, 16,17 we experimentally found that decomposition products deviate from earlier computationally predicted secondary phases. [35][36][37] Hence, experimental probing of these interfaces can not only help to elucidate fundamental mechanisms but also detect decomposition onset conditions which are important for validating and benchmarking computational predictions.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Moreover, practical consideration of the environment, such as temperature and gas species involved in the synthesis, is still difficult to simulate and can lead to divergences between computational predictions and experimental observations. For example, in our recent work on LLZO-NMC and LLZO-LCO interface, 16,17 we experimentally found that decomposition products deviate from earlier computationally predicted secondary phases. [35][36][37] Hence, experimental probing of these interfaces can not only help to elucidate fundamental mechanisms but also detect decomposition onset conditions which are important for validating and benchmarking computational predictions.…”
Section: Introductionmentioning
confidence: 79%
“…The approach for modelling the interfacial feature was adopted from previous studies. 16,53,54 Finally, the tail was modelled by using another constant phase element (CPE tail ) in series with the above circuit elements, as reported elsewhere to model Li-blocking Au electrode. 51,52 Fig.…”
Section: Interfacial Impedance As a Results Of Annealing In Airmentioning
confidence: 99%
See 3 more Smart Citations